2021
DOI: 10.1088/1748-605x/aba327
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Study on tensile, bending, fatigue, and in vivo behavior of porous SHS–TiNi alloy used as a bone substitute

Abstract: Intermetallic porous SHS–TiNi alloys exhibit tangled and specific stress–strain characteristics. This article aims to evaluate the findings emanating from experiments using standard and proprietary instruments. Fatigue testing under repeated complex loading was used to measure the total number of load cycles before failure of the SHS–TiNi samples occurred. Of the tested samples, seventy percent passed through 106 cycles without failure due to the reversible martensite transformation in the TiNi phase, one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The distinctive feature of porous TiNi is conditioned by the lowest elastic modulus similar to that demonstrated by the bone tissue. Additionally, the rheological resemblance in terms of stress-strain allows the artificial rib to be congruentially deformed without failure and delamination, passing through a million cycles, as recently assessed by Yasenchuk et al [ 23 ]. The rough, hydrophilic surface of porous SHS-TiNi was reported to sustain cell adhesion, growth, and proliferation via a system of interconnected macro-/micropores and grooves [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive feature of porous TiNi is conditioned by the lowest elastic modulus similar to that demonstrated by the bone tissue. Additionally, the rheological resemblance in terms of stress-strain allows the artificial rib to be congruentially deformed without failure and delamination, passing through a million cycles, as recently assessed by Yasenchuk et al [ 23 ]. The rough, hydrophilic surface of porous SHS-TiNi was reported to sustain cell adhesion, growth, and proliferation via a system of interconnected macro-/micropores and grooves [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are three categories of the SMA that have been put into application [1], the Ni based, the Copper based and the stainless steel based. The Nibased SMA, especially the NiTi SMA shows excellent properties such as Shape Memory Effect and superelastic [2,3], damping characteristics [4,5], corrosion resistance [6][7][8] and biocompatibility [9,10]. Based on these characteristics, Ni-based SMA has been widely used in aerospace, machinery, chemical, electronics and medical fields [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Porous and solid TiNi-based implants and their successful deployment in surgical treatments have encouraged insights for immediate and delayed rib-plasty in cancer patients. Experimental and clinical studies with promising results have demonstrated successful integration of TiNi implants with the formation of regenerated tissues, which anatomically and physiologically restore the injured area [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Recently, porous SHS-TiNi alloys have been reported [ 31 ] to have some features that significantly distinguish them from those manufactured by other methods of powder metallurgy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rheological similarity between the viscoelastic artificial TiNi sandwich and the rib imparts additional working benefits to this biomaterial. The distinctive feature of porous TiNi is conditioned by the lowest elastic modulus similar to that demonstrated by the bone tissue, whereas a rheological resemblance in terms of stress-strain allows the artificial rib to be congruentially deformed without rupture and delamination, passing through a million cycles, as studied in [ 30 ]. The rough hydrophilic surface of porous SHS-TiNi was reported to sustain cell adhesion, growth, and proliferation via a system of interconnected macro-/micropores and grooves [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%